Pemberdayaan Masyarakat melalui Pelatihan Pembuatan Abon Ikan Mujair Upaya Peningkatan Nilai Tambah Hasil Perikanan di Desa Gempolpendowo - Andayani, Aisyah Julia; Nataliawati, Rita; Hidayati, Ema; Mamduc, Akrom Fahmi; Sutiani, Sutiani; Putri Sholehah, Natasya Eka; Octaviani, Cindy; Bayhaqi, Moh. Nauval (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Gempolpendowo Village in Glagah District, Lamongan Regency, boasts abundant tilapia fish production but often faces price declines during peak harvests. This community service activity aims to improve the community's skills in fish processing diversification through training in tilapia floss production, packaging, and marketing strategies. The implementation method included preparation, outreach, hands-on training, mentoring discussions, and evaluation. The activity results demonstrated improved community skills in fish processing, a significant increase in the selling price from IDR 15,000/kg to IDR 40,000–50,000 per 250 grams of floss, and a growing entrepreneurial spirit, especially among housewives. The floss product has a longer shelf life and the potential for developing flavor variations to meet market needs. This activity is important because it not only increases community income and strengthens the village economy but also supports food security. Therefore, further assistance in digital marketing, branding, and product licensing is still needed for business sustainability.